Beyond migration—Chemokines in lymphocyte priming, differentiation, and modulating effector functions. Issue 2 (18th April 2018) - Laufer, Julia M.; Legler, Daniel F.
Abstract: Chemokines and their receptors coordinate the positioning of leukocytes, and lymphocytes in particular, in space and time. Discrete lymphocyte subsets, depending on their activation and differentiation status, express various sets of chemokine receptors to be recruited to distinct tissues. Thus, the network of chemokines and their receptors ensures the correct localization of specialized lymphocyte subsets within the appropriate microenvironment enabling them to search for cognate antigens, to become activated, and to fulfill their effector functions. The chemokine system therefore is vital for the initiation as well as the regulation of immune responses to protect the body from pathogens while maintaining tolerance towards self. Besides the well investigated function of orchestrating directed cell migration, chemokines additionally act on lymphocytes in multiple ways to shape immune responses. In this review, we highlight and discuss the role of chemokines and chemokine receptors in controlling cell‐to‐cell contacts required for lymphocyte arrest on endothelial cells and immunological synapse formation, in lymphocyte priming and differentiation, survival, as well as in modulating effector functions. Abstract : Review on functions of chemokines and their receptors in lymphocyte biology that go beyond guiding directional cell migration.